Insulin signalling requires glucose to promote lipid anabolism in adipocytes - Krycer, JR; Quek, L-E; Francis, D; Zadoorian, A; Weiss, FC; Cooke, KC; Nelson, ME; Diaz-Vegas, A; Humphrey, SJ; Scalzo, R; Hirayama, A; Ikeda, S; et al. (American Society for Biochemistry & Molecular Biology, 2020)
Adipose tissue is essential for metabolic homeostasis, balancing lipid storage and mobilisation based on nutritional status. This is coordinated by insulin, which triggers kinase signalling cascades to modulate numerous metabolic proteins, leading to increased glucose uptake and anabolic processes like lipogenesis. Given recent evidence that glucose is dispensable for adipocyte respiration, we sought to test whether glucose is necessary for insulin-stimulated anabolism. Examining lipogenesis in cultured adipocytes, glucose was essential for insulin to stimulate the synthesis of fatty acids and glyceride-glycerol. Importantly, glucose was dispensable for lipogenesis in the absence of insulin, suggesting distinct carbon sources are used with or without insulin. Metabolic tracing studies revealed glucose was required for insulin to stimulate pathways providing carbon substrate, NADPH, and glycerol 3’-phosphate for lipid synthesis and storage. Glucose also displaced leucine as a lipogenic substrate and was necessary to suppress fatty acid oxidation. Together, glucose provided substrates and metabolic control for insulin to promote lipogenesis in adipocytes. This contrasted with the suppression of lipolysis by insulin signalling, which occurred independently of glucose. Given previous observations that signal transduction acts primarily before glucose uptake in adipocytes, these data are consistent with a model whereby insulin initially utilises protein phosphorylation to stimulate lipid anabolism, which is sustained by subsequent glucose metabolism. Consequently, lipid abundance was sensitive to glucose availability, both during adipogenesis and in Drosophila flies in vivo. Together, these data highlight the importance of glucose metabolism to support insulin action, providing a complementary regulatory mechanism to signal transduction to stimulate adipose anabolism.